Standards to assure quality in nursing research - SCD Zeelie (AOSIS, 2003)
The focus of this article is quality assurance in nursing research. Due to well established problems regarding the education of nursing research and increasing pressure to take responsibility for the quality of all educational activities, departments of nursing are obliged to initiate action; to assure quality in nursing research. A nursing department functions within a well-defined external context. The external context comprises of various aspects such as rolplayer expectations and current educational and professional legislation. Standards are the basic components of any quality assurance system (Booyens, 1996:305). Standards give direction to the practitioner and must be compiled within the context of the country's cultural, philosophical and ethical value systems, as well as its social economic and political development.